2015
DOI: 10.1007/s00253-015-6818-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of whey proteins

Abstract: Milk contains an array of proteins with useful bioactivities. Many milk proteins encompassing native or chemically modified casein, lactoferrin, alpha-lactalbumin, and beta-lactoglobulin demonstrated antiviral activities. Casein and alpha-lactalbumin gained anti-HIV activity after modification with 3-hydroxyphthalic anhydride. Many milk proteins inhibited HIV reverse transcriptase. Bovine glycolactin, angiogenin-1, lactogenin, casein, alpha-lactalbumin, beta-lactoglobulin, bovine lactoferrampin, and human lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 75 publications
(92 reference statements)
0
52
0
9
Order By: Relevance
“…A panel of experimental assays has been established to study these mechanisms; the activity of Lf is screened by incubating cells with Lf before they are infected with viral particles [61]. The antiviral activity of Lf has mainly been studied in viruses that cause human diseases or can be transmitted from animals to humans: HIV, cytomegalovirus, hepatitis B and C virus, adenovirus, poliovirus, hantavirus, Sindbis virus, Semliki Forest virus, avian influenza A (H5N1), influenza virus A H1N1, respiratory syncytial virus, herpes simplex virus type 1 and type 2, echovirus, enterovirus, and rotavirus [62]. On the other hand, as Lf is a food component, it can be easily consumed by people to prevent common viral infections.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…A panel of experimental assays has been established to study these mechanisms; the activity of Lf is screened by incubating cells with Lf before they are infected with viral particles [61]. The antiviral activity of Lf has mainly been studied in viruses that cause human diseases or can be transmitted from animals to humans: HIV, cytomegalovirus, hepatitis B and C virus, adenovirus, poliovirus, hantavirus, Sindbis virus, Semliki Forest virus, avian influenza A (H5N1), influenza virus A H1N1, respiratory syncytial virus, herpes simplex virus type 1 and type 2, echovirus, enterovirus, and rotavirus [62]. On the other hand, as Lf is a food component, it can be easily consumed by people to prevent common viral infections.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…As indicated above, whey proteins display activity against a variety of viruses, such as Semliki forest virus, adenovirus, HCMV, HIV, enterovirus, rotavirus, Sindbis virus, echovirus, papillomavirus, hantavirus, HSV 1 and 2, respiratory syncytial virus, influenza virus H1N1, avian influenza virus H5N1, poliovirus, HBV, and HCV [86].…”
Section: Modifications Of Milk Proteins To Increase Their Antiviral Amentioning
confidence: 94%
“…Lactoferrin was first isolated by Sorensen and Sorensen [84] from bovine milk, and it is a non-haem iron-binding peptide that belongs to the transferrin family of proteins [85]. Lactoferrin has been reported to inhibit respiratory syncytial virus, hepatitis B virus (HBV), adenovirus, poliovirus, hantavirus, Sindbis virus, Semliki forest virus, echovirus, enterovirus, and rotavirus [86]. Ng et al also studied the antiviral activities of whey proteins [87] and found that some of them could inhibit the HIV reverse transcriptase ( Fig.…”
Section: 222mentioning
confidence: 99%
“…Эти свойства связаны с белками молокаказеином, лактальбумином, лактоферрином и другими. В частности, лактоферрин, гликолактин, ангиогенин-1, лактогенин, казеин, лактоферрампин, альфа-и беталактальбумины коровьего молока способны, в той или иной степени, подавлять ВИЧ-1 [11]. Сиализированные олигосахариды молока [12] подавляют вирусы гриппа (H1N1, H1N2, H3N2, H9N2).…”
unclassified
“…Наиболее выраженной ингибирующей способностью в отношении вирусов обладает лактоферрин (ЛФ). Известно, что лактоферрин подавляет активность штаммов вируса гриппа (H5N1, H1N1, H3N2), вируса полиомиелита, аденовируса, респираторно-синцитиального вируса человека, энтеровируса, ротавируса, вирусов гепатитов В и С, цитомегаловируса, вируса простого герпеса 1 и 2 типа, ВИЧ-1, вируса Зика, Денге и других [3,4,5,6,11,16].…”
unclassified